Proses Akuisisi Bahasa Kedua pada Anak - Nurqomariyyah, Afiva; Darni, Darni; Pairin, Udjang (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study focuses on the process of language acquisition, which is limited to children's language acquisition. The purpose of this research is to describe and analyze the process of language acquisition. For children aged 06. Data was collected using technical methods and Collect data step by step by interviewing your child's parents directly. Data collection, data analysis and presentation of analysis results. Results It was concluded that the factors that influence language acquisition in children are: Age factor, because at a young age it is easier for a child to master language. second; Elements of the first language (mother) because the first language has a great influence on grammar Different; Environmental factors, the environment is a very important factor to obtain The tongue of a six year old child acquires the language he often hears. environment, especially family, friends and society; biological and cognitive factors; Children under the age of 6 years are still in the stage of biological and cognitive development. Language acquisition - very often the addition and subtraction of words in pronunciation, It is natural and over time a child, even a child and more mature, both biologically and cognitively.